Pengaruh Varian Produk dan Kemudahan Pembelian Terhadap Gaya Hidup Serta Implikasinya pada Keputusan Pembelian Es Krim Wedrink; Studi Kasus pada Pelajar SMA Kota Tebing Tinggi - Alvina Putri Yunita; Putri Yulandra; Daniel Collyn; Nursaimatussaddiya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the Influence of Product Variants and Ease of Purchase on Lifestyle and Its Implications on Purchase Decisions for Wedrink Ice Cream. The research method used is a quantitative method using SmartPLS version 3.0. The questionnaire was distributed to 97 respondents. The data analysis method used in this study is the measurement model (outer model), namely the validity test, reliability test, then the structural model (inner model) including: coefficient of determination/r-square (r2) and hypothesis testing with t-statistics and indirect effect tests. The results of SmartPLS 3.0 in this research are that Lifestyle influences the decision to purchase WeDrink ice cream among high school students in Tebing Tinggi City, Ease of Purchase influences the Decision to Purchase WeDrink ice cream among high school students in Tebing Tinggi City, Product Variants do not influence the Decision to Purchase WeDrink ice cream among students in Tebing Tinggi City, Ease of Purchase influences Lifestyle among high school students in Tebing Tinggi City, Product Variants influence Lifestyle among high school students in Tebing Tinggi City, Ease of Purchase influences Purchase Decisions through Lifestyle of high school students in the city of Tebing Tinggi, product variants influence purchasing decisions through the lifestyle of high school students in the city of Tebing Tinggi.